From IT service management to IT service governance: An ontological approach for integrated use of ITIL and COBIT frameworks - Lamia Moudoubah; Abir El Yamami; Khalifa Mansouri; Mohammed Qbadou (Institute of Advanced Engineering and Science, 2021)
Some companies have achieved better performance as a result of their IT investments, while others have not, as organizations are interested in calculating the value added by their IT. There is a wide range of literature that agrees that the best practices used by organizations promote continuous improvement in service delivery. Nevertheless, overuse of these practices can have undesirable effects and unquantified investments. This paper proposed a practical tool formally developed according to the DSR design science approach, it addresses a domain relevant to both practitioners and academics by providing IT service governance (ITSG) domain model ontology, concerned with maximizing the clarity and veracity of the concepts within it. The results revealed that the proposed ontology resolved key barriers to ITSG process adoption in organizations, and that combining COBIT and ITIL practices would help organizations better manage their IT services and achieve better business-IT alignment.